The Contributing Factors of Pragmatic Failure in Uzbek’s ELT Classrooms - Saidova Mukhayyo Umedilloevna (Genius Journals, 2023)
Pragmatic failure is the inability to understand what is meant by what is said, which can often lead to misunderstanding or confusion in cross-cultural communication. For this reason, the present article explores the contributing factors of pragmatic failure in Uzbek’s ELT Classrooms. The following factors as teacher-centered teaching; lack of authentic input; teaching English without considering the cultural differences; linguistic competence oriented evaluation system were found out.
Keywords: pragmatic failure; contributing factors; culture; cultivation